DNA Barcoding Elucidates Cyprinid Reproductive Interactions in a Southwest Virginia Stream. Issue 1 (2nd December 2016) - Peoples, Brandon K.; Cooper, Pearce; Frimpong, Emmanuel A.; Hallerman, Eric M.
Abstract: Chubs Nocomis spp. (Cyprinidae) in freshwater streams build conspicuous gravel mounds upon which they and other nest‐associative cyprinids spawn. Our understanding of such interactions is incomplete and hindered by the inability to observe all interactions directly and to identify the larvae that emerge from the mounds based on morphological traits. We used visual surveys and DNA barcoding to identify cyprinids that were associated with the nests of spawning chub in Catawba Creek, a small tributary of the James River in southwestern Virginia. All individual fish on nests were identified to species and categorized as spawning or feeding. Eggs were subsequently removed from the nests and hatched in captivity, and DNA was extracted from the larvae. The DNA sequences for region 3 of the mitochondrial cytochrome‐ c oxidase I gene in individual larvae were amplified, and the resulting sequences were compared to entries in GenBank by using the Basic Local Alignment Search Tool for nucleotide data. Of the 75 larval fish that were assayed, 56 (75%) were genetically identified. Species‐level identification of the larval cyprinids was straightforward except with regard to Nocomis, for which cryptic taxonomy is currently unresolved. Four cyprinid species were identified among the larvae sampled from Nocomis nests; of those species, the Central Stoneroller Campostoma anomalum and Rosyside Dace Clinostomus funduloides had not been previously witnessed to spawn on chub nests. Central Stonerollers had been observed to perform activities that were more indicative of nest predation than spawning; hence, the presence of their eggs on Nocomis nests suggests that the activity of Central Stonerollers is not entirely antagonistic. Received June 2, 2016; accepted September 19, 2016 Published online December 2, 2016